1986
DOI: 10.1002/jlb.40.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Luminol-Dependent Chemiluminescence of Stimulated Rat Alveolar Macrophages by Pretreatment With Alveolar Lining Material

Abstract: Previous reports indicate that the in vitro bactericidal activity of rat alveolar macrophages (AM) is dependent on the lipid fraction (ALM-L) of the alveolar lining material (ALM). The present study demonstrates that luminol-dependent chemiluminescence of stimulated rat AM is increased when rat AM are preincubated in the ALM or in the ALM-L. Evidence is presented that oxidation of the unsaturated lipids is responsible for the increase. In addition to pretreatment with the ALM, cells were also pretreated in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 14 publications
2
10
1
Order By: Relevance
“…It has been shown that the amount of CL produced depends on the extent of ingested particles (29). We did not observe an increased generation of CL in monocytes preincubated with Curosurf, although this has previously been described in rat alveolar macrophages pretreated with several unsaturated lipids (30). In a recent study, a suppressive effect of rabbit lung surfactant on CL generated by rabbit alveolar macrophages was demonstrated; again, lipid components were thought to be responsible for this alteration of cell function (3 1).…”
Section: Discussioncontrasting
confidence: 78%
“…It has been shown that the amount of CL produced depends on the extent of ingested particles (29). We did not observe an increased generation of CL in monocytes preincubated with Curosurf, although this has previously been described in rat alveolar macrophages pretreated with several unsaturated lipids (30). In a recent study, a suppressive effect of rabbit lung surfactant on CL generated by rabbit alveolar macrophages was demonstrated; again, lipid components were thought to be responsible for this alteration of cell function (3 1).…”
Section: Discussioncontrasting
confidence: 78%
“…Moreover, the active concentrations of the surfactant preparations (100 -500 g/ml) are consistent with reported in vivo concentrations (20). Surfactant has previously been reported to enhance (42), suppress (20,21), or have no effect on the production of superoxide by alveolar macrophages or monocytes (34). However, the different models and methods used have probably contributed to the conflicting reports.…”
Section: Discussionsupporting
confidence: 60%
“…Since natural surfactant was more active, surfactant apoprote'ins were also believed to be involved in this process. In contrast, Webb and Jeska [21] found enhanced luminol-dependent CL of rat alveolar macrophages by pretreatment with the lipid fraction from the alveolar lining material and subsequent stimulation with latex beads. Van Iwaarden et al [22] recently published data, indicating an increase of lucigenin-dependent CL of rat alveolar macrophages by human SP-A and rat surfactant without further stimuli.…”
Section: Discussionmentioning
confidence: 81%